Structure Characterization of Phospholipids and Lipid a of Pseudomonas Putida KT2442. Issue 5 (October 2015) - Wang, Yuqian; Wang, Jianli; Li, Ye; Wang, Biwen; Tao, Guanjun; Wang, Xiaoyuan
Pseudomonas putida KT2442 is an important bacterium for producing various types of polyhydroxyalkanoate polymers. Phospholipids and lipid A in membranes of P. putida play important roles in stress responses, but detailed structural information of these lipids is not known. In this study, phospholipids and lipid A were isolated from P. putida KT2442, and their structures were analyzed using thin layer chromatography, high performance liquid chromatography and electrospray ionization/mass spectrometry. Major phospholipids in P. putida KT2442 were phosphatidylethanolamine (79.9%), phosphatidylglycero1 (12.7%) and cardiolipin (7.4%), with C16:1 and/or C18:1 acyl chains. Four lipid A species were found in P. putida KT2442: two are hexa-acylated and the other two are penta-acylated. Compared with lipid A of P. aeruginosa, P. putida lipid A has less hydroxylation on the secondary acyl chains and less modification. Therefore, P. putida lipid A could be used as a base structure to investigate lipid A modification of P. aeruginosa for understanding its pathogenesis.